RNA kink-turns as molecular elbows: hydration, cation binding, and large-scale dynamics - Rázga, Filip; Zacharias, Martin; Réblová, Kamila; Koca, Jaroslav; Sponer, Jirí (Structure (London, England, 2006)
The presence of Kink-turns (Kt) at key functional sites in the ribosome (e.g., A-site finger and L7/L12 stalk) suggests that some Kink-turns can confer flexibility on RNA protuberances that regulate the traversal of tRNAs during translocation. Explicit solvent molecular dynamics demonstrates that Kink-turns can act as flexible molecular elbows. Kink-turns are associated with a unique network of long-residency static and dynamical hydration sites that is intimately involved in modulating their conformational dynamics. An implicit solvent conformational search confirms the flexibility of Kink-turns around their X-ray geometries and identifies a second low-energy region with open structures that could correspond to Kink-turn geometries seen in solution experiments. An extended simulation of Kt-42 with the factor binding site (helices 43 and 44) shows that the local Kt-42 elbow-like motion fully propagates beyond the Kink-turn, and that there is no other comparably flexible site in this rRNA region. Kink-turns could mediate large-scale adjustments of distant RNA segments.
Keywords: kationty; Nucleic Acid Conformation; Cations; krystalografie rentgenová; RNA ribozomální; vazebná místa; Crystallography, X-Ray; RNA, Ribosomal; Binding Sites; konformace nukleové kyseliny